Astrocyte-Derived Pleiotrophin Mitigates Late-Stage Autoimmune CNS Inflammation - Linnerbauer, Mathias; Lößlein, Lena; Farrenkopf, Daniel; Vandrey, Oliver; Tsaktanis, Thanos; Naumann, Ulrike; Rothhammer, Veit (Frontiers in Immunology, 2022)
Astrocytes are the most abundant glial cells in the central nervous system (CNS) with the capacity to sense and react to injury and inflammatory events. While it has been widely documented that astrocytes can exert tissue-degenerative functions, less is known about their protective and disease-limiting roles. Here, we report the upregulation of pleiotrophin (PTN) by mouse and human astrocytes in multiple sclerosis (MS) and its preclinical model experimental autoimmune encephalomyelitis (EAE). Using CRISPR-Cas9-based genetic perturbation systems, we demonstrate in vivo that astrocyte-derived PTN is critical for the recovery phase of EAE and limits chronic CNS inflammation. PTN reduces pro-inflammatory signaling in astrocytes and microglia and promotes neuronal survival following inflammatory challenge. Finally, we show that intranasal administration of PTN during the late phase of EAE successfully reduces disease severity, making it a potential therapeutic candidate for the treatment of progressive MS, for which existing therapies are limited.
CRIS-Team Scopus Importer:2022-01-28
Keywords: astrocytes; autoimmunity; CNS inflammation; multiple sclerosis; protective

Intranasal delivery of a small-molecule ErbB inhibitor promotes recovery from acute and late-stage CNS inflammation - Linnerbauer, Mathias; Lößlein, Lena; Vandrey, Oliver; Tsaktanis, Thanos; Beer, Alexander; Naumann, Ulrike; Panier, Franziska; Beyer, Tobias; Nirschl, Lucy; Kuramatsu, Joji; Winkler, Jürgen; Quintana, Francisco J.; et al. (JCI Insight, 2022)
Multiple sclerosis (MS) is an autoimmune inflammatory disease of the CNS that is characterized by demyelination and axonal degeneration. Although several established treatments reduce relapse burden, effective treatments to halt chronic progression are scarce. Single-cell transcriptomic studies in MS and its animal models have described astrocytes and their spatial and functional heterogeneity as important cellular determinants of chronic disease. We combined CNS single-cell transcriptome data and small-molecule screens in primary mouse and human astrocytes to identify glial interactions, which could be targeted by repurposing FDA-approved small-molecule modulators for the treatment of acute and late-stage CNS inflammation. Using hierarchical in vitro and in vivo validation studies, we demonstrate that among selected pathways, blockade of ErbB by the tyrosine kinase inhibitor afatinib efficiently mitigates proinflammatory astrocyte polarization and promotes tissue-regenerative functions. We found that i.n. delivery of afatinib during acute and late-stage CNS inflammation ameliorates disease severity by reducing monocyte infiltration and axonal degeneration while increasing oligodendrocyte proliferation. We used unbiased screening approaches of astrocyte interactions to identify ErbB signaling and its modulation by afatinib as a potential therapeutic strategy for acute and chronic stages of autoimmune CNS inflammation.
CRIS-Team Scopus Importer:2022-04-22

PD-L1 positive astrocytes attenuate inflammatory functions of PD-1 positive microglia in models of autoimmune neuroinflammation - Linnerbauer, Mathias; Beyer, Tobias; Nirschl, Lucy; Farrenkopf, Daniel; Lößlein, Lena; Vandrey, Oliver; Peter, Anne; Tsaktanis, Thanos; Kebir, Hania; Laplaud, David; Oellinger, Rupert; Engleitner, Thomas; et al. (Nature Communications, 2023)
Multiple Sclerosis (MS) is a chronic autoimmune inflammatory disorder of the central nervous system (CNS). Current therapies mainly target inflammatory processes during acute stages, but effective treatments for progressive MS are limited. In this context, astrocytes have gained increasing attention as they have the capacity to drive, but also suppress tissue-degeneration. Here we show that astrocytes upregulate the immunomodulatory checkpoint molecule PD-L1 during acute autoimmune CNS inflammation in response to aryl hydrocarbon receptor and interferon signaling. Using CRISPR-Cas9 genetic perturbation in combination with small-molecule and antibody-mediated inhibition of PD-L1 and PD-1 both in vivo and in vitro, we demonstrate that astrocytic PD-L1 and its interaction with microglial PD-1 is required for the attenuation of autoimmune CNS inflammation in acute and progressive stages in a mouse model of MS. Our findings suggest the glial PD-L1/PD-1 axis as a potential therapeutic target for both acute and progressive MS stages.
CRIS-Team Scopus Importer:2023-09-22

Regulation of the programmed cell death protein 1/programmed cell death ligand 1 axis in relapsing-remitting multiple sclerosis - Tsaktanis, Thanos; Linnerbauer, Mathias; Lößlein, Lena; Farrenkopf, Daniel; Vandrey, Oliver; Peter, Anne; Cirac, Ana; Beyer, Tobias; Nirschl, Lucy; Grummel, Verena; Mühlau, Mark; Bussas, Matthias; et al. (Brain Communications, 2023)
The programmed cell death protein 1/programmed cell death ligand 1 axis plays an important role in the adaptive immune system and has influence on neoplastic and inflammatory diseases, while its role in multiple sclerosis is unclear. Here, we aimed to analyse expression patterns of programmed cell death protein 1 and programmed cell death ligand 1 on peripheral blood mononuclear cells and their soluble variants in multiple sclerosis patients and controls, to determine their correlation with clinical disability and disease activity. In a cross-sectional study, we performed in-depth flow cytometric immunophenotyping of peripheral blood mononuclear cells and analysed soluble programmed cell death protein 1 and programmed cell death ligand 1 serum levels in patients with relapsing-remitting multiple sclerosis and controls. In comparison to control subjects, relapsing-remitting multiple sclerosis patients displayed distinct cellular programmed cell death protein 1/programmed cell death ligand 1 expression patterns in immune cell subsets and increased soluble programmed cell death ligand 1 levels, which correlated with clinical measures of disability and MRI activity over time. This study extends our knowledge of how programmed cell death protein 1 and programmed cell death ligand 1 are expressed in the membranes of patients with relapsing-remitting multiple sclerosis and describes for the first time the elevation of soluble programmed cell death ligand 1 in the blood of multiple sclerosis patients. The distinct expression pattern of membrane-bound programmed cell death protein 1 and programmed cell death ligand 1 and the correlation between soluble programmed cell death ligand 1, membrane-bound programmed cell death ligand 1, disease and clinical factors may offer therapeutic potential in the setting of multiple sclerosis and might improve future diagnosis and clinical decision-making.
CRIS-Team Scopus Importer:2023-09-15
Keywords: autoimmunity; checkpoint; co-regulation; neuroinflammation; PBMCs

The astrocyte-produced growth factor HB-EGF limits autoimmune CNS pathology - Linnerbauer, Mathias; Lößlein, Lena; Vandrey, Oliver; Peter, Anne; Han, Yanan; Tsaktanis, Thanos; Wogram, Emile; Needhamsen, Maria; Kular, Lara; Nagel, Lisa; Zißler, Julia; Andert, Marie; et al. (Nature Immunology, 2024)
Central nervous system (CNS)-resident cells such as microglia, oligodendrocytes and astrocytes are gaining increasing attention in respect to their contribution to CNS pathologies including multiple sclerosis (MS). Several studies have demonstrated the involvement of pro-inflammatory glial subsets in the pathogenesis and propagation of inflammatory events in MS and its animal models. However, it has only recently become clear that the underlying heterogeneity of astrocytes and microglia can not only drive inflammation, but also lead to its resolution through direct and indirect mechanisms. Failure of these tissue-protective mechanisms may potentiate disease and increase the risk of conversion to progressive stages of MS, for which currently available therapies are limited. Using proteomic analyses of cerebrospinal fluid specimens from patients with MS in combination with experimental studies, we here identify Heparin-binding EGF-like growth factor (HB-EGF) as a central mediator of tissue-protective and anti-inflammatory effects important for the recovery from acute inflammatory lesions in CNS autoimmunity. Hypoxic conditions drive the rapid upregulation of HB-EGF by astrocytes during early CNS inflammation, while pro-inflammatory conditions suppress trophic HB-EGF signaling through epigenetic modifications. Finally, we demonstrate both anti-inflammatory and tissue-protective effects of HB-EGF in a broad variety of cell types in vitro and use intranasal administration of HB-EGF in acute and post-acute stages of autoimmune neuroinflammation to attenuate disease in a preclinical mouse model of MS. Altogether, we identify astrocyte-derived HB-EGF and its epigenetic regulation as a modulator of autoimmune CNS inflammation and potential therapeutic target in MS.
CRIS-Team Scopus Importer:2024-03-08